Efektivitas Media Pembelajaran Berbasis Android untuk Meningkatkan Hasil Belajar Mikrometer Sekrup - Ramdhan Akmaludin; Muhammad Khumaedi; Khoirul Huda (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study analyzes the impact of Android-based learning media on improving the competence of reading external micrometer screw scales at SMK Negeri 1 Karangdadap, Pekalongan Regency. This study used a quasi-experimental two-group pretest-posttest design in two eleventh grade classes of Light Vehicle Engineering. Data were collected through cognitive tests. Media analysis used the Content Validity Ratio (CVR) and Percent Agreement (PA). Statistical analysis of student learning outcomes used a two-tailed t-test to test pre-test results, while to test post-test results used descriptive analysis, normality test, homogeneity test, right-tailed t-test, and N-Gain. The pre-test results showed that the two groups' results did not differ, indicating that their initial abilities were similar. The right-tailed t-test results indicated an increase in learning outcomes after using Android-based learning media. The magnitude of the increase was measured using N-Gain, with the experimental group achieving an N-Gain of 55.49% (moderate) and the control group achieving 22.04% (low). Based on the results of this study, the recommendation that learning using Android-based media is effective in improving learning outcomes.